The ancient quarrel between philosophy and poetry revisited : Plato and the Greek literary tradition - Levin, Susan B., 1961- (Oxford Univ. Press, 2001)
In this study, Levin explores Plato's engagement with the Greek literary tradition in his treatment of key linguistic issues. This investigation, conjoined with a new interpretation of the Republic's familiar critique of poets, supports the view that Plato's work represents a valuable precedent for contemporary reflections on ways in which philosophy might benefit from appeals to literature.